DETAIL ENDOSCOPIC EXAMINATION RESULTS IN DISEASE PATIENTS AT Dr. DJAMIL PADANG HOSPITAL - Gangga Mahatma; Abdullah, Dessy; Elvi Fitraneti; Gustia Anjelika. A (Yayasan Nusantara Hasana Berdikari, 2024)
Background : Dyspepsia is a syndrome or a set of symptoms that arise due to abnormalities in the proximal digestive tract in the form of discomfort in the pit of the stomach or retrosternal pain, burning, bloating after eating, belching, nausea, vomiting, feeling full quickly and the stomach feels full. The emergency form of dyspeptic patients is the discovery of alarm symptoms. Patients with alarm symptoms have a high risk of malignancy for that patient should be investigated by endoscopic examination. Aims: This study aims to determine and identify the description of the results of endoscopic examination in dyspeptic patients who have alarm symptoms at Dr. RSUP. M. Djamil in 2019-2020. Method: This type of research is a categorical descriptive study with a cross sectional study design. The study was conducted in December 2021. The sample of this study were all patients who met the inclusion criteria at RSUP Dr. M. Djamil Padang in 2019-2020 with 39 samples. The sampling technique was done by total sampling. The analysis uses univariate analysis to see the frequency and percentage of each variable using SPSS. Result : This study found that the highest age group was 56-65 years as many as 9 people (23.1%), the most gender, namely male as many as 21 people (53.8%). The most common danger sign found was gastrointestinal bleeding as much as 15 (25.9%). The most common endoscopic appearance found was Gastritis as much as 25 (45.5%). Conclusion: In this study, the highest age group was 56-65 years, most of which occurred in men, the most common danger sign was gastrointestinal bleeding and the most common endoscopic appearance found was Gastritis.